Advancements in research and clinical management of interstitial lung injury associated with ADC drugs administration in breast cancer - Jia-yu Zhu; Rui-yuan Jiang; Huan-ping Zhang; Zi-ru Fang; Huan-huan Zhou; Qing Wei; Xiaojia Wang (Discover Oncology)
Abstract Antibody–drug conjugates (ADCs) represent a novel class of targeted anti-tumor medications that utilize the covalent linkage between monoclonal antibodies and cytotoxic agents. This unique mechanism combines the cytotoxic potency of drugs with the targeting specificity conferred by antigen recognition. However, it is essential to recognize that many ADCs still face challenges related to off-target toxicity akin to cytotoxic payloads, as well as targeted toxicity and other potential life-threatening adverse effects, such as treatment-induced interstitial lung injury. Currently, of the four approved ADC drugs for breast cancer, several reports have documented post-treatment lung injury-related fatalities. As a result, treatment-induced interstitial lung injury due to ADC drugs has become a clinical concern. In this review article, we delve into the factors associated with ADC-induced interstitial lung injury in patients with advanced-stage breast cancer and highlight strategies expected to decrease the incidence of ADC-related interstitial lung injury in the years ahead. These efforts are directed at enhancing treatment outcomes in both advanced and early-stage cancer patients while also providing insights into the development and innovation of ADC drugs and bolstering clinicians’ understanding of the diagnosis and management of ADC-associated interstitial lung injury.